GRANGER CAUSALITY POLA KONSUMSI IKAN DI ACEH TENGAH MENGGUNAKAN ANALISISI VECTOR ERROR CORRECTION MODEL (VECM) - Yasrizal, Yasrizal; Ukhty, Nabila (JURNAL PERIKANAN TROPIS, 2019)
Development of human resources is very important in promoting economic growth, because humans are not only objects in development but also play a role as a subject. Stunting is a major problem that inhibits the quality of human resources, to reduce the amount of human development that lives by stunting is to increase the consumption of protein contained in fish. This study aimed to determine the pattern of fish consumption in Central Aceh and the variables that affect fish consumption. The analytical model used is the granger causality analysis, through the Vector Error Correction Model (VECM) analysis model. The results of this study indicate that the pattern of fish consumption in Central Aceh was not only influenced by income, but also influenced by the amount of chicken meat and egg consumption Increased income does not have a positive effect on increasing fish consumption but affects the amount of chicken meat and egg consumption. To increase the amount of fish consumption in Central Aceh, efforts to increase the amount of fish supply through local fish farming activities and the socialization of fish eating.